Genomic insights into a multidrug-resistant pandoraea apista clinical isolate carrying blaOXA-153 from China - Lirong Li; Yawen Zhang; Fang He; Ningjun wu (Journal of Global Antimicrobial Resistance)
Objectives: Pandoraea apista is notable for its multidrug resistance and is frequently identified in patients with cystic fibrosis or other chronic lung diseases, where it contributes to persistent lung infections. In this study, we describe a strain of P. apista harboring the blaOXA-153, isolated from the bronchoalveolar lavage (BAL) fluid of an inpatient in China. Methods: The genomic DNA of P. apista strain PA167 was sequenced using the Illumina NovaSeq 6000 system and assembled with SPAdes v.3.13.0. Antimicrobial resistance genes (ARGs) were identified using ResFinder v.3.2 within the ABRicate v.0.9.0. Phylogenetic analysis was performed using the Snippy v.4.6.0. Results: The genome sequence of P. apista strain PA167 comprises 5,580,873 bp, with 4,926 protein-coding sequences, 4 ncRNAs, 59 tRNAs, and 3 rRNA operons. Only one ARG was identified: blaOXA-153. PA167 exhibited resistance to multiple antibiotics, including cephalosporins and carbapenems, and was susceptible only to sulfamethoxazole/trimethoprim. Twenty-four P. apista strains, including PA167, could be retrieved from the NCBI database, all carrying the blaOXA-153. Complete genomic sequencing of five strains confirmed the chromosomal presence of blaOXA-153. The isolation sources of these 24 strains were predominantly clinical samples, mainly respiratory specimens, with some strains isolated from environmental sources. Conclusion: Here, we present the genome sequence of a P. apista strain carrying the blaOXA-153, marking the first isolation of this strain from a clinical setting in China. The potential for future epidemic spread highlights the necessity for targeted antimicrobial strategies.